Safety of Alternative Antiviral Agents for Neonatal Herpes Simplex Virus Encephalitis and Disseminated Infection - Wang, Yu (Pediatric Pharmacy Advocacy Group, 2014)
OBJECTIVE: To review the evidence describing the safety of ganciclovir and foscarnet in neonates in order to guide treatment for central nervous system or disseminated herpes simplex infections in cases of acyclovir shortage or resistance. METHODS: PubMed, Ovid Medline, and International Pharmaceutical Abstracts were searched using the thesaurus and text-word terms “ganciclovir” and “foscarnet,” with birth to 1 month age limits. Thirty-two eligible publications describing safety in neonates were identified. RESULTS: In 340 neonates treated for cytomegalovirus (CMV), life-threatening neutropenia (absolute neutrophil count <0.5 × 10(9)/L) was reported in 8.8% of patients following up to 12 months of ganciclovir administered intravenously. Neutropenia and thrombocytopenia occurred in 25.6% and 6.2% of neonates, respectively. Changes in serum creatinine concentration of >0.2 mg/dL occurred in <1% of neonates. Hepatic transaminase increases or unspecified changes in liver function tests were reported in 6.2% of neonates with hyperbilirubinemia being observed in 3.5% of total neonates. Three out of four neonates receiving foscarnet for acyclovir-resistant herpes infection or CMV survived with minimal sequelae. Neither nephrotoxicity nor electrolyte or mineral imbalances were reported. CONCLUSIONS: Similar to what is seen in adolescents and adults, ganciclovir use in neonates is commonly associated with neutropenia, and the frequency of occurrence is comparable. The link between hepatotoxicity and ganciclovir should be interpreted with caution because of overlapping clinical manifestations of CMV. Only case reports are available describing foscarnet use in neonates, but adverse drug reactions were not observed. More research on these two agents is needed to draw conclusions about adverse drug reaction rates in the neonatal population.